Free thiomalate in plasma and urine of patients receiving sodium aurothiomalate. Issue 1 (February 1984) - Rudge, S R; Perrett, D; Swannell, A J
Abstract : Free thiomalate is measureable in the plasma and urine of patients with rheumatoid arthritis receiving sodium aurothiomalate (Myocrisin). Plasma concentrations and urinary excretion of free thiomalate were measured in 8 patients by high-performance liquid chromatography and electrochemical detection. After an initial intramuscular dose of 20 mg sodium aurothiomalate, free thiomalate was detected in plasma within 15 min, peak levels of up to 600 nmol/l occurring at 30 min. Plasma levels declined rapidly thereafter. During the first 24 h between 2 and 16% of the injected dose of aurothiomalate was recovered in the urine as free thiomalate, maximum excretion occurring during the first hour.